Sistema presupuestal - Pérez Díaz, Valentín; Plata Romero, Israel; Romero Fernández, Martha Beatriz; Vázquez León, Jazmín (My University, 2023)
Sistema presupuestal
Keywords: Sindicato; Calcular presupuesto; Redes; Diagrama de flujo; Windows XP